The training needs of Vocational Education Training (VET) called Audiovisual Projects and Performances derived from the COVID-19 crisis - Jambrina Rodríguez, Julia; Nieto-Ortiz, Jorge (Avances en Supervisión Educativa, 2022)
On Saturday, March 14, 2020, the “state of alarm” was activated in Spain to face the expansion of COVID-19 with various measures, among which the total confinement of the population and the paralysis of non-essential activities stand out. This study addresses that the official curriculum for the Vocational Education Training called Audiovisual Projects and Performances no longer adjusts to the unprecedented labor market. Likewise, the new reality is mainly based on the provision of services through technology and many of the competences that students assimilate during the learning of Vocational Training have been made obsolete by this paradigm shift. Although, little by little, investigations are being developed from different public and private organizations, many do not show sufficient scientific rigor and are distributed as initial surveys. For this reason, the approach we present is eminently bibliographic in the absence of more objective quantitative data that shows the true impact. The results indicated that the last Prospecting and Detection of Training Needs Report dates from 2017 and is incomplete for the Image and Sound professional career; that the confinement caused by COVID-19 has negatively affected the cultural industry and the normal development of its education; that new labor markets are emerging that require other competencies from students not contemplated in the current curriculum whose emphasis is on the audiovisual market. In conclusion, this paradigm shift requires a review of the curriculum as well as prospective studies and detection of new training needs.
Keywords: Vocational Education Training; COVID-19; film industry; performing arts; cultural industry